ANDES: a Tool for Evaluating Parallel Systems - Kitajima, João Paulo; Plateau, Brigitte (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 1995)
This paper presents the ANDESenvironment, a tool for supporting the performance evaluation of parallel systems. ANDES is structured as a modular tool. The parallel program, the parallel computer and the strategies used for implementing the software on the hardware are described separately. The interaction among modules occur when using ANDES. This environment is employed during the early phases of the software or hardware design. The evaluation technique currently adopted is based on the execution of synthetic workloads. However, ANDES can be used with other techniques that are compatible with the information described inside each module. A first prototype of the tool is running on a Transputer network. A more recent version runs on a computer network supporting PVM (Parallel Virtual Machine). ANDES was used to compare different mapping algorithms.